2021
DOI: 10.1029/2020gc009575
|View full text |Cite
|
Sign up to set email alerts
|

A 1200 ka Stable Isotope Record From the Center of the Badain Jaran Desert, Northwestern China: Implications for the Variation and Interplay of the Westerlies and the Asian Summer Monsoon

Abstract: The variation and interplay of westerlies and the Asian summer monsoon (ASM) are important for understanding climate change in the Northern Hemisphere. Yet their spatial and temporal evolution is still debatable. Here, we present a stable isotopic record from the center of the Badain Jaran Desert, in Northwestern China, which records the variations and interplay of the two climate systems during the past 1200 ka. The results indicate that the westerlies dominated the Badain Jaran area at least from 1200 to 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
(250 reference statements)
0
3
0
Order By: Relevance
“…In addition, as the species have well adapted to the arid environment, aridification associated with glaciation would not exert much stress on its persistence. On the contrary, the consequential expansion of desert environments might have opened up an array of new habitats for arid species ( Wang et al 2021 ). For example, the expansion of dune fields during glacial periods ( Dong et al 2013 ; Lu et al 2013 ) would provide M. mongolicus with a suitable matrix for burrowing, by which they could effectively buffer the climate extremes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as the species have well adapted to the arid environment, aridification associated with glaciation would not exert much stress on its persistence. On the contrary, the consequential expansion of desert environments might have opened up an array of new habitats for arid species ( Wang et al 2021 ). For example, the expansion of dune fields during glacial periods ( Dong et al 2013 ; Lu et al 2013 ) would provide M. mongolicus with a suitable matrix for burrowing, by which they could effectively buffer the climate extremes.…”
Section: Discussionmentioning
confidence: 99%
“…Through the study of the stable isotopes of carbonates in the sediment cores from the hinterland of the Badanjilin Desert, one of the typical areas of interaction of the westerlies and ASM in the desert zone of northern China, Wang F et al [44] found that, during the period of 1200-600 ka B.P, the δ 18 O and δ 13 C values showed a common trend of collaborative increase (Figure 2C). This is consistent with the research results of carbonate carbon isotopes in the Cretaceous red layers dominated by the planetary wind system before the Late Oligocene, reflecting intense evaporation under the control of a dry climate.…”
Section: The Relationship and Interaction Between The Westerlies And ...mentioning
confidence: 99%
“…This is consistent with the research results of carbonate carbon isotopes in the Cretaceous red layers dominated by the planetary wind system before the Late Oligocene, reflecting intense evaporation under the control of a dry climate. Therefore, it is argued that, during the period of 1200-600 ka B.P., the area was controlled by the Westerly circulation [44]. In addition, the carbonate isotopes of δ 18 O and δ 13 C from sediment cores in the western Qaidam Basin in the northern Qinghai-Tibet Plateau, which is dominated by the Westerlies, also showed a synergistic increase trend during the period of 1200-600 ka B.P.…”
Section: The Relationship and Interaction Between The Westerlies And ...mentioning
confidence: 99%